A baseline process for the production, recovery, and purification of bacterial influenza vaccine candidates. (8th June 2013) - Sánchez‐Arreola, Pamela B.; López‐Uriarte, Salvador; Marichal‐Gallardo, Pável A.; González‐Vázquez, Juan C.; Pérez‐Chavarría, Roberto; Soto‐Vázquez, Pedro; López‐Pacheco, Felipe; Ramírez‐Medrano, Alicia; Rocha‐Pizaña, María R.; Álvarez, Mario M.
<x xml:space="preserve">Abstract</x> The current commercial system for influenza vaccine production depends on the culture of virus in embryonated eggs—a strategy that is both costly and poorly scalable. Consequently, a sudden pandemic event with a demand for millions of vaccine doses in a short time could readily overwhelm the available world production capacity. In this communication, we present a process that uses Escherichia coli for scalable production of recombinant vaccine candidates against influenza. A monomeric and a dimeric fragment of hemagglutinin of the influenza A H1N1/2009 virus were successfully expressed in a BL21 (DE3) pLysS variety of C41 E. coli. We present results from batch processes where induction is made with isopropyl thiogalactoside and from fed‐batch experiments where expression is induced using lactose/glucose pulses. Concentrations in the range of 1.188–0.605 g/L of recombinant protein were observed in 2‐L stirred tank bioreactors. The genetic construct included an N‐terminal histidine tag sequence that facilitated recovery, purification, and proper refolding of the vaccine candidate by affinity chromatography in columns loaded with Ni+2. The proteins produced by this strategy selectively and specifically recognizes antibodies from patients diagnosed as positive to influenza A H1N1/2009. Overall protein recovery yields between 30.0 and 34.7% were typically observed. Based on these yields, a production of 4.6 × 103 doses L−3 day−1 is feasible. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 29:896–908, 2013